AN OBSERVATIONAL STUDY REGARDING VARIOUS AETIOLOGICAL FACTORS IN VATARAKTA - Arya Archana; Tripathi Sanjay Kr; Shukla Shweta (International Journal of Ayurveda and Pharma Research, 2021)
Objective: The prime causative factors of Vatarakta are Vata Dosha and Rakta Dhatu which vitiates by their own different Nidana simultaneously and later on vitiates each other. This study mainly aims to assess the aetiological factors in Vatarakta patients and to identify the common causative factors that causes Vatarakta which are already mentioned in the Samhitas. Methods: An observational study was conducted in Rishikul Ayurvedic Hospital among 30 patients. Data was obtained by assessing the diet and lifestyle related etiological factors of the patients. Results: Majority of the patients (60%) were in the age group of 30-40 years. Most common Aharaj aetiological factors observed in this study were Katu Bhojan (60%) and Lavan Bhojan (67%) while Viharaj aetiological factors were Ratrijagrana (24%) and Achankramansheela (50%). Conclusion: It is concluded that life style and food habit changes are responsible for the disease Vatarakta. A proper wholesome diet and physical activity must be adopted to fight with this disease.